Accuracy of pregnancy diagnosis in swine by ultrasonography - Williams, Sara Inés (2008)
Early and accurate diagnosis of nonpregnant sows and gilts has the potential to increase reproductive efficiency and the financial income in pig production by reducing non-productive days per sow per year. The objectives of this study were to compare the efficiency of pregnancy diagnosis between Doppler Echo+ and real time ultrasonography (RTU) and to compare the efficiency by using RTU at different days post-mating (days 17 to 24) under commercial conditions. In the 1st study, using crossbreed sows and gilts (n=107), pregnancy diagnoses were done with Doppler Echo+ and then with RTU. Between 28 and 65 days of gestation, Doppler Echo+ had 85% sensitivity and 32% specificity, and efficiency was 73%. In the 2nd study, sows (n=142) were scanned for pregnancy diagnosis between 17 and 24 d post-mating (PD1) and reconfirmed between 38 and 45 days of gestation (PD2). After 21 days of gestation, RTU had over 90% sensitivity and 45% specificity, and 70% efficiency. Accuracy between PD1-farrowing was 75.5% and between PD1 and PD2 was 80.6%. In the 3rd study, sows were diagnosed pregnant by RTU (n=151) at 17 to 24 days of gestation or A-mode ultrasound (n=172) at 28 to 30 days of gestation. There were no significant differences in conception rate (P > 0.09) and farrowing rate (P > 0.67) between both groups. Hence, there was no improvement in fertility and farrowing rate by using RTU instead of A-mode ultrasound under commercial conditions. -17.1.1.38.